2020
DOI: 10.1177/1010428320958603
|View full text |Cite
|
Sign up to set email alerts
|

A continuous responder algorithm to optimize clinical management of small-cell lung cancer with progastrin-releasing peptide as a simple blood test

Abstract: This study aimed to investigate whether changes in progastrin-releasing peptide (ProGRP) levels correlate with treatment response and can be used to optimize clinical management of patients with small-cell lung cancer. Patients with small-cell lung cancer (any stage) receiving chemotherapy were eligible. ProGRP was measured in serum/plasma at baseline and after each chemotherapy cycle using the Elecsys® ProGRP assay (Roche Diagnostics). Treatment response was assessed by computed tomography scan. The primary o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…Ming LI 1,# , Yi ZHANG 2,# , Li JIANG 3 , Yan LI 4 , Gang LI 5 , Jianping ZHOU 6 , Chen YANG 7 , Xinhui LI 8 , Wei QU 9 , Yong CHEN 10 , Qing CHEN 10 , Shukui WANG 11, *, Jinliang XING 12, *, Huayi HUANG 10,13…”
Section: New Insights Into the Diagnostic Characteristics And Clinica...mentioning
confidence: 99%
See 1 more Smart Citation
“…Ming LI 1,# , Yi ZHANG 2,# , Li JIANG 3 , Yan LI 4 , Gang LI 5 , Jianping ZHOU 6 , Chen YANG 7 , Xinhui LI 8 , Wei QU 9 , Yong CHEN 10 , Qing CHEN 10 , Shukui WANG 11, *, Jinliang XING 12, *, Huayi HUANG 10,13…”
Section: New Insights Into the Diagnostic Characteristics And Clinica...mentioning
confidence: 99%
“…Numerous reports have indicated that some serum biomarkers had a fair diagnostic or prognostic performance for lung cancer. In addition, the elevation of these biomarkers could serve as a sign of distant metastasis [6,7]. Nevertheless, reports concerning the diagnostic performance of serum biomarkers on lung cancer were still inconsistent and debatable, thus the biomarkers are underutilized in clinical practice in general.…”
mentioning
confidence: 99%
“…The 7.7 levels of NSE were at a time when the disease was stable. In a recent study by Muley et al .., Pro-GRP levels were found to be reliable and repeatable method in monitoring the disease in response to chemotherapy [16].…”
Section: Discussionmentioning
confidence: 99%
“…NSE increases in some cases of SCLC, however, the specificity and sensitivity are NS enough to consider as a diagnostic tool [15]. Progastrin releasing peptide (PRO-GRP) is a circulating marker that may have beneficial use in diagnosing SCLC [16]. It has been shown that PRO-GRP has a higher sensitivity and specificity than NSE [15,17].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous reports indicated that some biomarkers had a fair diagnostic or prognostic performance for lung cancer. In addition, elevation of these biomarkers could serve as sign of distant metastasis [6,7]. Nevertheless, reports concerning the diagnostic performance of biomarkers on lung cancer were still inconsistent and even contradictory, thus the markers are underutilized in clinical practice in general.…”
Section: Introductionmentioning
confidence: 99%